Application of a self-designed multifunction lower limb function training device in patients undergoing lower extremity orthopedic surgery (自制多功能下肢功能锻炼装置在下肢骨科手术患者中的应用) - CHEN Xi (陈熙) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of multifunction lower limb function training device in patients undergoing lower extremity orthopedic surgery. Methods Totally 122 patients undergoing lower extremity orthopedic surgery were randomly divided into the study group(n=62) and control group (n=60). The control group received routine postoperative function training guided by verbal guidance and demonstration, and the multifunction lower limb function training device was used for postoperative function training in the study group. The incidence of deep venous thrombosis of the lower extremity (DVT), degree of patient satisfaction, qualified rate of function training and incidences of other lower limb complications were compared between groups. Results The incidence of DVT in the study group was lower than that in the control group (P＜0. 05). The qualified rate of function training in the study group were higher than that in the control group (P＜0. 05). Conclusion The self-designed multifunction lower limb function training device can promote effective lower-limb training for patients undergoing lower extremity orthopedic surgery and reduce the risk of DVT after surgery. (目的 探讨自制多功能下肢功能锻炼装置在行下肢骨科手术患者中的应用效果。方法 选取2021年4月-12月在医院住院治疗的行下肢骨科手术患者122例为研究对象, 随机分为研究组(n=62)和对照组(n=60)。对照组按照传统的口头指导、示范等宣教方法行术后功能锻炼; 研究组应用自制多功能下肢功能锻炼装置进行康复锻炼。通过比较术后两组患者下肢深静脉血栓形成(DVT)发生率、功能锻炼达标率和其他下肢并发症发生率等指标来进行效果评估。结果 研究组患者术后下肢DVT发生率低于对照组, 功能锻炼达标率高于对照组, 差异有统计学意义(P＜0. 05)。结论 多功能下肢功能锻炼装置简单易操作, 能使下肢骨科手术患者早期主动进行有效的下肢康复锻炼, 有效预防DVT发生, 从而达到预期功能锻炼效果。)